A polylactic acid electric energy metering box composite material and a reaction extrusion preparation method thereof

CN122541970BActive Publication Date: 2026-09-11ZHEJIANG HANGZHOU ZHAN HOLDINGS CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611052294.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-09-11
Estimated Expiration
2046-07-15

AI Technical Summary

Technical Problem

[0003]然而,聚乳酸材料在实际应用中仍面临诸多技术瓶颈

Benefits of technology

1.本发明通过分段喂料反应挤出工艺,补偿了聚乳酸在熔融加工过程中因热降解导致的分子量下降,同时构建了适度的交联网络结构,提高了复合材料的熔体强度和热稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122541970B_ABST
    Figure CN122541970B_ABST
Patent Text Reader

Abstract

This invention belongs to the field of polymer composite material technology, specifically relating to a polylactic acid (PLA) power metering box composite material and its reactive extrusion preparation method. Addressing the long-term weather resistance and aging issues of PLA composite materials in complex outdoor environments, this invention involves pre-mixing PLA resin with a nucleating agent and toughening agent after vacuum drying, then feeding it into the first stage of an extruder through the main feed port for plasticization. Next, a crosslinking agent and stannous octoate are added to the first side feed port for chain extension and crosslinking reaction. Then, a UV-absorbing monomer containing olefinic unsaturated double bonds and an initiator are added to the second side feed port for melt graft polymerization. After homogenization, extrusion, pelletizing, and drying, the PLA composite material is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer composite materials technology, specifically relating to a polylactic acid (PLA) energy metering box composite material and its reactive extrusion preparation method. Background Technology

[0002] Polylactic acid (PLA) is a fully biodegradable polyester polymer material made from renewable plant resources such as corn and sugarcane. It possesses excellent biocompatibility, mechanical properties, and electrical insulation properties. Electricity metering boxes are typically located outdoors or in semi-outdoor environments, and the box materials must withstand the combined effects of sunlight, rain, thermal cycling, humidity, electric fields, dust, and contaminants. Currently, commonly used materials for electricity metering boxes include PC, PC / ABS, SMC, and unsaturated polyester glass fiber reinforced materials.

[0003] However, polylactic acid (PLA) materials still face many technical bottlenecks in practical applications. First, PLA itself is brittle, lacks heat resistance, and has a low heat distortion temperature, making it prone to deformation in high-temperature outdoor environments. Second, the PLA molecular chain contains ester bonds, which are susceptible to hydrolysis and photodegradation under humid environments and ultraviolet light, leading to a sharp decline in the material's mechanical properties.

[0004] In the prior art, publication number CN114806117A discloses a polylactic acid shell for an electricity metering box and its preparation method. The method involves blending polylactic acid with phase change microcapsules, using the phase change microcapsules to inhibit the development of electrical trees and thus delay the electro-aging process. The preparation of this document focuses on the phase change microcapsules and their blending with PLA, without involving in-situ grafting of ultraviolet absorption structures onto the PLA molecular chain, nor does it reduce the molecular weight decrease caused by outdoor damp heat and photo-oxidative aging through diisocyanate segmental chain extension.

[0005] In summary, there is an urgent need for a material and a new preparation method that can simultaneously solve the problems of insufficient toughness and poor outdoor weather resistance of polylactic acid. Summary of the Invention

[0006] This invention provides a polylactic acid (PLA) energy metering box composite material and its reactive extrusion preparation method.

[0007] The specific technical solution is as follows: A reactive extrusion method for preparing polylactic acid (PLA) energy metering box composite material is as follows: S1: Premixing. Polylactic acid resin, nucleating agent, toughening agent, and UV-absorbing monomer are pre-dried. The dried polylactic acid resin, nucleating agent, and toughening agent are premixed, and the temperature is controlled at ≤60℃. The mixture is then discharged to obtain the premixed material.

[0008] S2: Segmented feeding. The premix prepared in S1 is added through the main feed port and melted and plasticized. Then, the crosslinking agent and stannous octoate are added through the first side feed port for crosslinking reaction. Finally, the UV-absorbing monomer and initiator are added through the second side feed port for melt grafting and homogenization treatment to obtain a mixture.

[0009] S3: Post-processing, the mixture prepared in S2 is extruded, cooled, pelletized, and dried to obtain polylactic acid composite material.

[0010] Furthermore, the polylactic acid resin described in S1 is one or more of L-polylactic acid, D-polylactic acid, or racemic polylactic acid.

[0011] The nucleating agent mentioned in S1 is one or more of ethylene bis-stearamide, talc, and montmorillonite.

[0012] The toughening agent described in S1 is one or more of polybutylene adipate terephthalate, polycaprolactone, polyethylene glycol, and natural rubber.

[0013] The pre-drying process described in S1 has the following parameters: polylactic acid resin drying temperature 90℃, vacuum degree -0.09MPa, duration 6h, moisture content controlled <0.02%, nucleating agent drying temperature 95℃, duration 3h, toughening agent drying temperature 70℃, duration 5h, and UV absorption monomer drying temperature 50℃, duration 3h.

[0014] The premixing described in S1 has the following parameter settings: rotation speed 500-1500 rpm, duration 5-15 min.

[0015] Furthermore, the parameters for the melt plasticization described in S2 are set as follows: temperature 160–190°C.

[0016] The crosslinking agent described in S2 is one or more of hexamethylene diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate.

[0017] The cross-linking reaction described in S2 has the following parameters: temperature 170-200℃, duration 1-5 min.

[0018] The ultraviolet-absorbing monomer described in S2 is one of 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole and 2-hydroxy-4-acryloyloxybenzophenone.

[0019] The initiator mentioned in S2 is one of benzoyl peroxide and dicumyl peroxide.

[0020] The parameters for the fusion grafting described in S2 are: temperature 165-195℃, duration 2-6min.

[0021] The homogenization process described in S2 has the following parameters: temperature 170–190°C, duration 1–3 min.

[0022] Furthermore, the drying process described in S3 has the following parameters: temperature 80–100°C, vacuum degree -0.09 MPa, and duration 4–12 hours.

[0023] The polylactic acid composite material described in S3, based on 100 parts of polylactic acid resin, contains 0.5 to 3 parts of nucleating agent, 5 to 20 parts of toughening agent, 0.5 to 3 parts of crosslinking agent, 0.05 to 0.3 parts of stannous octoate, 1 to 5 parts of ultraviolet absorbing monomer, and 0.1 to 0.5 parts of initiator.

[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention compensates for the decrease in molecular weight of polylactic acid due to thermal degradation during melt processing by using a segmented feeding reactive extrusion process, while constructing a moderate cross-linked network structure, thereby improving the melt strength and thermal stability of the composite material.

[0025] 2. This invention uses an initiator to chemically bond ultraviolet absorbing functional groups to the polylactic acid molecular chain in the form of covalent bonds, thereby endowing the composite material with durable and stable ultraviolet absorption and light stabilization functions. Attached Figure Description

[0026] Figure 1 These are the microstructure and crack density diagrams of the polylactic acid composite materials finally prepared in Examples 1-3 and Comparative Examples 1-3, where H1-H3 are Examples 1-3 and C1-C3 are Comparative Examples 1-3.

[0027] Figure 2 These are three-dimensional deformation cloud maps of the polylactic acid composite materials finally prepared in Example 1 and Comparative Example 1.

[0028] Figure 3 The graphs show the leakage current curves of the polylactic acid composite materials finally prepared in Examples 1-3 and Comparative Examples 1-3, where H1-H3 represent Examples 1-3 and C1-C3 represent Comparative Examples 1-3.

[0029] Figure 4 This is a diagram showing the retention rate of the locking force of the polylactic acid composite materials finally prepared in Examples 1-3 and Comparative Examples 1-3, where H1-H3 represent Examples 1-3 and C1-C3 represent Comparative Examples 1-3.

[0030] Figure 5 These are comparison images of the polylactic acid composite materials finally prepared in Examples 1-3 and Comparative Examples 1-3 after aging. H1-H3 represent Examples 1-3, and C1-C3 represent Comparative Examples 1-3. Detailed Implementation

[0031] The following embodiments further explain and illustrate the technical solutions of the present invention. It should be specifically noted that each specific embodiment is a concretization and explanation of the technical solution and should not be considered as a limitation on the scope of protection of the present invention. Those skilled in the art still have the right to modify the technical solutions of these embodiments and make equivalent substitutions for some or all of the technical features, and these modifications or substitutions do not change the essence of the corresponding technical solutions, nor do they cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions described in the present invention.

[0032] This invention proposes a polylactic acid (PLA) composite material for an energy metering box and its reactive extrusion preparation method, the detailed technical solution of which is as follows: 1. Premix Polylactic acid resin, nucleating agent, toughening agent, and UV-absorbing monomer are pre-dried. The dried polylactic acid resin, nucleating agent, and toughening agent are then pre-mixed at a temperature of ≤60℃ and discharged to obtain a premixed material.

[0033] During the mixing process, the materials flow in a fluidized state within the mixing container, creating strong turbulence and material exchange. This promotes the uniform distribution of each component on a macroscopic scale. Simultaneously, under shearing action, frequent contact and collisions occur between the toughening agent and the polylactic acid (PLA) resin particles. The toughening agent molecular chains gradually unfold at the interface and partially embed into the surface micropores of the PLA resin particles, forming preliminary physical entanglement and interfacial wetting. This interfacial wetting effect helps reduce the interfacial tension between the two phases during subsequent melt blending, promoting the fine dispersion of the toughening agent in the PLA matrix. Furthermore, it breaks down easily agglomerated nucleating agents into primary particles or small agglomerates, ensuring their uniform coating on the surface of the PLA resin particles.

[0034] 2. Segmented feeding The premix is ​​added through the main feed port and melted and plasticized. Then, the crosslinking agent and stannous octoate are added through the first side feed port for crosslinking reaction. Finally, the UV-absorbing monomer and initiator are added through the second side feed port for melt grafting and homogenization to obtain the mixture.

[0035] The crosslinking agent contains two isocyanate groups, which have extremely high reactivity and can undergo addition reactions with compounds containing active hydrogen. The polylactic acid (PLA) molecular chain has hydroxyl and carboxyl end groups, respectively. Under the catalysis of stannous octoate, the isocyanate groups react with the hydroxyl groups to form urethane bonds and with the carboxyl groups to form amide bonds, releasing carbon dioxide. When the diisocyanate reacts with the PLA molecular chain with multiple end groups, a moderately crosslinked three-dimensional network structure can be formed, compensating for the decrease in molecular weight of PLA due to thermal degradation during melt processing, and improving the melt strength and thermal stability of PLA.

[0036] The initiator undergoes homolytic cleavage of the O-O bond under heating conditions, decomposing to generate benzoyloxy free radicals. The benzoyloxy free radicals can be further decarboxylated to generate phenyl free radicals. The primary free radicals abstract hydrogen atoms from the polylactic acid molecular chain, forming macromolecular free radicals on the polylactic acid molecular chain. The macromolecular free radicals initiate chain growth reactions in the UV-absorbing monomers containing olefinic unsaturated double bonds, covalently bonding the UV-absorbing functional groups to the polylactic acid molecular chain. Compared with the traditional method of adding UV absorbers through physical blending, this method avoids the problems of migration, precipitation, and volatilization of UV absorbers during long-term use.

[0037] The core of segmented feeding lies in separating the chain extension crosslinking reaction and the graft polymerization reaction in terms of time and space: First, it avoids interference between reactants. If all components are added at once, the chain extender and the graft polymerization initiator will coexist in the same reaction system. The -NCO groups in the diisocyanate may react with the free radicals generated by the decomposition of the initiator; and the olefinic unsaturated double bonds in the UV-absorbing monomer may undergo thermal polymerization under the chain extension crosslinking reaction conditions. These interferences will seriously affect the efficiency of the two reactions and the performance of the products. Second, although the optimal temperature for the chain extension crosslinking reaction and the optimal temperature for the graft polymerization reaction are similar, they are still different, and their required optimal residence times are different. The segmented design allows each step of the reaction to be carried out in its own independent temperature control zone, making temperature and residence time control more precise. At the same time, the chain extension crosslinking reaction is carried out first, and the graft polymerization reaction is carried out after the molecular weight of polylactic acid increases and a moderate crosslinking network is formed. This can avoid the over-crosslinking or gelation problems that may occur when graft polymerization is carried out in low molecular weight polylactic acid melt.

[0038] 3. Post-processing The mixture is extruded, cooled, pelletized, and dried to obtain a polylactic acid composite material.

[0039] The polylactic acid (PLA) composite melt extruded from the die is in a completely molten amorphous state. When the hot strip enters the cooling water bath, heat is transferred to the cooling water through the strip's surface, causing the strip temperature to drop rapidly. As the temperature falls below the glass transition temperature of PLA, the movement of PLA molecular chain segments is frozen, and the strip transitions from a highly elastic state to a glassy state, achieving solidification. Rapid cooling helps freeze the PLA molecular chains in an amorphous state, inhibiting the formation of large spherulites and maintaining the material's transparency; while a moderate cooling rate avoids internal stress and shrinkage pores caused by sudden cooling.

[0040] Example 1 A polylactic acid (PLA) composite material for an energy metering box and its reactive extrusion preparation method are as follows: Table 1 Main Raw Materials ; S1: Premixing: Polylactic acid resin is pre-dried at a vacuum of -0.09 MPa and a temperature of 90°C for 6 hours, with the moisture content controlled at <0.02%. The nucleating agent is dried at a temperature of 95°C for 3 hours, the toughening agent is dried at a temperature of 70°C for 5 hours, and the UV-absorbing monomer is dried at a temperature of 50°C for 3 hours. 100g of dried polylactic acid resin (dextral polylactic acid), 1.75g ​​of nucleating agent (ethylene bis-stearamide), and 13g of toughening agent (polybutylene adipate terephthalate) are premixed at 1000rpm for 10 minutes, with the temperature controlled at ≤60°C. The mixture is then discharged to obtain the premixed material.

[0041] S2: Segmented feeding. The premix prepared in S1 is added through the main feed port and melt-plasticized at 175℃. Then, 1.8g of crosslinking agent (hexamethylene diisocyanate) and 0.64g (0.18 parts based on effective ingredients; 0.64g of actual feed is used when using 28% commercial product) of stannous octoate are added through the first side feed port. The crosslinking reaction is carried out at 185℃ for 3 minutes. Then, 3g of UV-absorbing monomer (2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole) and 0.3g of initiator (benzoyl peroxide) are added through the second side feed port. The mixture is melt-grafted at 180℃ for 4 minutes and homogenized at 180℃ for 2 minutes to obtain the mixture.

[0042] S3: Post-processing, the mixture prepared in S2 is extruded, cooled, pelletized, and dried (temperature 90℃, vacuum degree -0.09MPa, time 8h) to obtain polylactic acid composite material.

[0043] Example 2 The composition and preparation process are the same as in Example 1, except that: In the preparation process S1, the polylactic acid resin is L-polylactic acid, the nucleating agent is montmorillonite, the toughening agent is polycaprolactone, and the other components are the same.

[0044] The premixing parameters in step S1 of the preparation process are set as follows: rotation speed 500 rpm, duration 5 min, and other steps are the same.

[0045] In the preparation process S2, the crosslinking agent is toluene diisocyanate, the ultraviolet absorbing monomer is 2-hydroxy-4-acryloyloxybenzophenone, the initiator is dicumyl peroxide, and the other components are the same.

[0046] Example 3 The composition and preparation process are the same as in Example 1, except that: In the preparation process S1, the polylactic acid resin is racemic polylactic acid, the nucleating agent is talc, the toughening agent is polyethylene glycol, and the other components are the same.

[0047] The premixing parameters in step S1 of the preparation process are set as follows: rotation speed 1500 rpm, duration 15 min, and other steps are the same.

[0048] In step S2 of the preparation process, the crosslinking agent is diphenylmethane diisocyanate, and the other components are the same.

[0049] Example 4 The composition and preparation process are the same as in Example 1, except that: In the preparation process S2, the crosslinking reaction parameters were set as follows: temperature 170℃, duration 1min; the melt grafting parameters were set as follows: temperature 165℃, duration 2min; the homogenization treatment parameters were set as follows: temperature 170℃, duration 1min; and other steps were the same.

[0050] The drying parameters in step S3 of the preparation process are set as follows: temperature 80℃, vacuum degree -0.09MPa, duration 4h, and other steps are the same.

[0051] The polylactic acid composite material in the S3 preparation process, by weight, is based on 100 parts of polylactic acid resin, with 0.5 parts of nucleating agent, 5 parts of toughening agent, 0.5 parts of crosslinking agent, 0.05 parts of stannous octoate, 1 part of ultraviolet absorbing monomer, 0.1 parts of initiator, and other components being the same.

[0052] Example 5 The composition and preparation process are the same as in Example 1, except that: In the preparation process S2, the crosslinking reaction parameters were set as follows: temperature 200℃, duration 5min; the melt grafting parameters were set as follows: temperature 195℃, duration 6min; the homogenization treatment parameters were set as follows: temperature 190℃, duration 3min; and other steps were the same.

[0053] The drying parameters in step S3 of the preparation process are set as follows: temperature 100℃, vacuum degree -0.09MPa, duration 12h, and other steps are the same.

[0054] The polylactic acid composite material in the S3 preparation process, by weight, is based on 100 parts of polylactic acid resin, with 3 parts of nucleating agent, 20 parts of toughening agent, 3 parts of crosslinking agent, 0.3 parts of stannous octoate, 5 parts of ultraviolet absorbing monomer, 0.5 parts of initiator, and other components being the same.

[0055] Example 6 The composition and preparation process are the same as in Example 1, except that: In the preparation process S1, the polylactic acid resin is a mixture of dextrorotatory polylactic acid and racemic polylactic acid in a mass ratio of 1:1, the nucleating agent is a mixture of talc powder and montmorillonite in a mass ratio of 1:0.5, the toughening agent is natural rubber, and the other components are the same.

[0056] The premixing parameters in step S1 of the preparation process are set as follows: rotation speed 1200 rpm, duration 12 min, and other steps are the same.

[0057] In the preparation process S2, the crosslinking agent is a mixture of hexamethylene diisocyanate and toluene diisocyanate in a molar ratio of 1:1, and the other components are the same.

[0058] The polylactic acid composite material in the S3 preparation process, by weight, is based on 100 parts of polylactic acid resin, with 2 parts of nucleating agent, 10 parts of toughening agent, 1 part of crosslinking agent, 0.1 parts of stannous octoate, 4 parts of ultraviolet absorbing monomer, 0.4 parts of initiator, and other components being the same.

[0059] Example 7 The composition and preparation process are the same as in Example 1, except that: In the preparation process S1, the nucleating agent is a mixture of ethylene bis-stearamide and montmorillonite in a mass ratio of 1:1, and the other components are the same.

[0060] In the preparation process S2, the crosslinking reaction parameters were set as follows: temperature 190℃, duration 2min; the melt grafting parameters were set as follows: temperature 170℃, duration 5min; the homogenization treatment parameters were set as follows: temperature 187℃, duration 1.5min; and other steps were the same.

[0061] The drying parameters in step S3 of the preparation process are set as follows: temperature 95℃, vacuum degree -0.09MPa, duration 9h, and other steps are the same.

[0062] The polylactic acid composite material in preparation process S3, by weight, is based on 100 parts of polylactic acid resin, with 1 part of nucleating agent, 17 parts of toughening agent, 2 parts of crosslinking agent, 0.2 parts of stannous octoate, 2 parts of ultraviolet absorbing monomer, 0.2 parts of initiator, and other components being the same.

[0063] Comparative Example 1 The composition and preparation process are the same as in Example 1, except that: In step S2 of the preparation process, no diisocyanate chain extender / crosslinker and stannous octoate catalyst are added, meaning that the chain extension / crosslinking reaction step is not performed; the other steps are the same.

[0064] Comparative Example 2 The composition and preparation process are the same as in Example 1, except that: In the preparation process S2, no UV-absorbing monomers containing olefinic unsaturated double bonds and initiators are added, that is, the melt graft polymerization reaction step is not carried out, and the other steps are the same.

[0065] Comparative Example 3 The composition and preparation process are the same as in Example 1, except that: In step S2 of the preparation process, the UV absorber is added by physical blending, specifically by adding the UV absorber directly from the main feed port, with the other steps being the same.

[0066] Based on Examples 1-7 and Comparative Examples 1-3, samples of the finally prepared polylactic acid composite materials were taken for tensile strength retention tests: the material was injection molded into dumbbell-shaped specimens, which were then placed in an environment of 23°C and 50% relative humidity for 96 hours. The width and thickness of the working section of each specimen were measured, and the average value of multiple measurements was taken. The specimens were divided into an initial group and an aging group. The initial group was tested using a universal testing machine (tensile rate 5 mm / min), and its maximum tensile force was recorded to obtain the initial tensile strength. The aging group was placed in an aging test chamber and aged under a xenon lamp for 960 hours (irradiance of 0.51 W / (m²) at 340 nm). 2 (nm), black standard temperature 65℃, relative humidity 50%, drying for 102 min, spraying for 18 min), then take it out and place it in an environment with temperature 23℃ and relative humidity 50% for 4 h. Repeat the above initial group test steps to obtain the tensile strength after aging. Finally, compare to obtain the tensile strength retention rate. Measure 5 groups and take the average value.

[0067] Based on Examples 1-7 and Comparative Examples 1-3, samples of the finally prepared polylactic acid composite materials were taken for impact strength retention tests: The material was injection molded into flat specimens (80mm × 10mm × 4mm). An A-type notch (root radius 0.25mm, notch depth 2mm) was machined in the middle of the specimen. The specimens were then placed in an environment of 23℃ and 50% relative humidity for 96 hours. The remaining width at the notch of each specimen was measured, and the specimens were divided into an initial group and an aged group. The initial group specimens were vertically clamped in the testing machine fixture, with the notch facing the opposite side of the pendulum impact direction. The impact energy absorbed when the specimen fractured was recorded to obtain the initial impact strength. The aged group specimens were placed in an aging test chamber and aged under a xenon lamp for 960 hours (irradiance of 0.51W / (m²) at 340nm). 2 (nm), black standard temperature 65℃, relative humidity 50%, drying for 102 min, spraying for 18 min), then take it out and place it in an environment with temperature 23℃ and relative humidity 50% for 4 h. Repeat the above initial group test steps to obtain the impact strength after aging. Finally, compare to obtain the impact strength retention rate. Measure 5 groups and take the average value.

[0068] Combining Examples 1-7 and Comparative Examples 1-3, samples of the finally prepared polylactic acid composite material were taken for flexural strength retention tests: The material was injection molded into flat specimens (80mm × 10mm × 4mm) and placed in an environment of 23℃ and 50% relative humidity for 96 hours. The width and thickness were measured at the center of the specimen length and 20mm from the center, dividing the specimens into an initial group and an aged group. The support span (L = (16±1) × h) was set according to the thickness of the initial group specimens, and tests were conducted (bending speed 2mm / min). The maximum bending force was recorded, and the initial flexural strength was calculated. The aged group was placed in an aging chamber and aged under a xenon lamp for 960 hours (irradiance of 0.51W / (m²) at 340nm). 2 (nm), black standard temperature 65℃, relative humidity 50%, drying for 102 min, spraying for 18 min), then take it out and place it in an environment with temperature 23℃ and relative humidity 50% for 4 h. Repeat the above initial group test steps to obtain the bending strength after aging. Finally, compare to obtain the bending strength retention rate. Measure 5 groups and take the average value.

[0069] Based on Examples 1-7 and Comparative Examples 1-3, samples of the finally prepared polylactic acid composite material were taken and subjected to volume resistivity testing: the material was injection molded into a flat sample (100mm×100mm×2mm), the sample surface was cleaned with anhydrous ethanol, and then placed in an environment of 23°C and 50% relative humidity for 24 hours. A test voltage of 500V was applied for 60 seconds, and the stable volume current was read. Multiple measurements were taken until the deviation of 5 consecutive readings was within 5%, and the volume resistivity was calculated.

[0070] Samples of the polylactic acid composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were taken and prepared into flat samples (100mm×100mm×2mm). These samples were conditioned for 24 hours at 23℃ and 50% relative humidity, and then aged in an aging chamber under a xenon lamp for 960 hours (irradiance of 0.51 W / (m²) at 340nm). 2 (nm), black mark temperature 65℃, relative humidity 50%, drying for 102 min, spraying for 18 min), morphology testing was performed. SEM test samples were then sputtered with gold. H1-H3 are Examples 1-3, C1-C3 are Comparative Examples 1-3, as shown below. Figure 1 As shown, H1-H3 have low surface crack density, and under SEM, they are mainly characterized by slight scratches, shallow microcracks, or local roughness. The 3D morphology shows little variation, indicating that the chain extension crosslinking network and chemically grafted UV absorption structure can inhibit surface cracking induced by photo-oxidation and hydrolysis. C1 has the highest crack density and the largest crack width. C2 has an increased number of cracks and surface roughness. After aging, the crack density of C3 is lower than that of C1 / C2 but still higher than that of H1-H3.

[0071] Samples of the polylactic acid composite materials prepared in Example 1 and Comparative Example 1 were taken and prepared into power metering box samples. These samples were conditioned for 24 hours at 23°C and 50% relative humidity, and then aged in an aging chamber using a xenon lamp for 960 hours (irradiance of 0.51 W / (m²) at 340 nm). 2 (nm), black standard temperature 65℃, relative humidity 50%, drying for 102 min, spraying for 18 min), and three-dimensional deformation test were performed, such as Figure 2 As shown.

[0072] Samples of the polylactic acid composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were taken and prepared into power metering box samples. These samples were conditioned for 24 hours at 23°C and 50% relative humidity, and then aged in an aging chamber under a xenon lamp for 960 hours (irradiance of 0.51 W / (m²) at 340 nm). 2 (nm), black mark temperature 65℃, relative humidity 50%, drying for 102 min, spraying for 18 min), then perform live leakage current test (temperature 50℃, relative humidity 90%, spraying for 18 min / drying for 102 min cycle, duration 960 h, test voltage 500V), record stable leakage current at 0, 240, 480, 720, and 960 h, such as Figure 3 As shown, the current curve of the example sample is close to horizontal because it has fewer cracks, fewer moisture absorption channels, and maintains a high volume resistivity, while the current of the comparative sample increases significantly over time.

[0073] Samples of the polylactic acid composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were taken and prepared into power metering box samples. These samples were conditioned for 24 hours at 23°C and 50% relative humidity, and then aged in an aging chamber under a xenon lamp for 960 hours (irradiance of 0.51 W / (m²) at 340 nm). 2 (nm), black standard temperature 65℃, relative humidity 50%, drying 102min, spraying 18min), hinge, latch and screw post holding force test was performed using a universal testing machine (tensile speed 10mm / min), screw post pull-out speed was 5mm / min, such as Figure 4 As shown, the retention rate of the sample in the embodiment was maintained at about 86% to 95%, indicating that the functional structure of the box was not significantly brittle. The retention rate of the comparative sample decreased, indicating that the reliability of the latch closure, door opening and closing, and screw fixing was insufficient.

[0074] Samples of the polylactic acid composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were taken and prepared into power metering box samples. These samples were conditioned for 24 hours at 23°C and 50% relative humidity, and then aged in an aging chamber under a xenon lamp for 960 hours (irradiance of 0.51 W / (m²) at 340 nm). 2(nm), black mark temperature 65℃, relative humidity 50%, drying for 102 min, spraying for 18 min), and observe the appearance of the actual product. Figure 5 As shown, the sample in the example has slight color difference or slight cracks, the comparative examples 1 and 2 show cracks and powdering, and the comparative example 3 shows whitening, precipitation and cracks.

[0075] The specific test results are shown in Table 2. Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 As shown: Table 2 Comparison of core performance between Examples 1-7 and Comparative Examples 1-3 ; The comparison results above show that Example 1 exhibits the best overall performance. The chemically bonded UV-absorbing functional groups, the chain-extending crosslinking network reinforcing the molecular skeleton, and the synergistic effect of the toughening agent demonstrate that Example 1 successfully solves the current problems of weather resistance and aging of polylactic acid composites in complex outdoor environments. Examples 2 to 7 show slightly lower overall performance than Example 1 but still maintain a high level, indicating excellent weather resistance and anti-aging effects even with a wide range of parameter variations. In Comparative Example 1, because the chain-extending crosslinking reaction step was not performed, the PLA molecular chains rapidly hydrolyzed and broke under the synergistic effects of water, light, heat, and oxygen. Comparative Example 2, lacking the melt grafting polymerization reaction step, lacked a chemically grafted UV-absorbing structure in its composite material. UV radiation directly acted on the PLA molecular chains, triggering photo-oxidative degradation. In Comparative Example 3, the UV absorber was added through physical blending, but the UV absorber gradually migrated and precipitated, failing to effectively solve the long-term weather resistance problem.

[0076] In summary, it can be clearly seen from the above embodiments and comparative examples that the polylactic acid (PLA) energy metering box composite material provided by the present invention has a significant improvement in weather resistance and anti-aging properties. This is attributed to the synergistic technical solution of constructing a PLA matrix, chain extension crosslinking, and chemical grafting of benzotriazole monomers, thereby solving the weather resistance and aging problems of PLA energy metering box composite material in complex outdoor environments.

Claims

1. A reactive extrusion preparation method for a polylactic acid (PLA) energy metering box composite material, characterized in that: The polylactic acid (PLA) power metering box composite material is prepared by reactive extrusion of the following raw materials in parts by weight: based on 100 parts of PLA resin, 0.5-3 parts of nucleating agent, 5-20 parts of toughening agent, 0.5-3 parts of diisocyanate crosslinking agent, 0.05-0.3 parts of stannous octoate, 1-5 parts of UV-absorbing monomer containing olefinic unsaturated double bonds, and 0.1-0.5 parts of initiator; The diisocyanate crosslinking agent is one or more of hexamethylene diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; the UV-absorbing monomer containing an olefinic unsaturated double bond is one of 2-(2′-hydroxy-5′-methacryloyloxyethylphenyl)-2H-benzotriazole and 2-hydroxy-4-acryloyloxybenzophenone; and the initiator is benzoyl peroxide or dicumyl peroxide. The method includes the following steps: S1: Premixing: Polylactic acid resin, nucleating agent, toughening agent, and UV-absorbing monomer are pre-dried, and the moisture content of polylactic acid resin is controlled to be <0.02%. The dried polylactic acid resin, nucleating agent, and toughening agent are premixed, and the temperature is controlled to be ≤60℃. The material is discharged to obtain the premixed material. S2: Segmented feeding. The premix prepared in S1 is added through the main feed port and melted and plasticized. Then, the crosslinking agent and stannous octoate are added through the first side feed port for crosslinking reaction. Finally, the UV-absorbing monomer and initiator are added through the second side feed port for melt grafting and homogenization treatment to obtain a mixture. S3: Post-processing, the mixture prepared in S2 is extruded, cooled, pelletized, and dried to obtain polylactic acid composite material.

2. The reactive extrusion preparation method of polylactic acid power metering box composite material according to claim 1, characterized in that: The nucleating agent is one or more of ethylene bis-stearamide, talc, and montmorillonite.

3. The reactive extrusion preparation method of a polylactic acid (PLA) energy metering box composite material according to claim 1, characterized in that: The toughening agent is one or more of polybutylene adipate terephthalate, polycaprolactone, polyethylene glycol, and natural rubber.

4. The reactive extrusion preparation method of a polylactic acid energy metering box composite material according to claim 1, characterized in that: The polylactic acid resin described in S1 is one or more of L-polylactic acid, D-polylactic acid, or racemic polylactic acid. The pre-drying process described in S1 has the following parameters: polylactic acid resin drying temperature 90℃, vacuum degree -0.09MPa, duration 6h, moisture content controlled <0.02%, nucleating agent drying temperature 95℃, duration 3h, toughening agent drying temperature 70℃, duration 5h, and UV absorption monomer drying temperature 50℃, duration 3h. The premixing described in S1 has the following parameter settings: rotation speed 500-1500 rpm, duration 5-15 min.

5. The reactive extrusion preparation method of a polylactic acid energy metering box composite material according to claim 1, characterized in that: The melt plasticization described in S2 has the following parameter settings: temperature 160~190℃; The cross-linking reaction described in S2 has the following parameters: temperature 170-200℃, duration 1-5 min.

6. The reactive extrusion preparation method of a polylactic acid (PLA) energy metering box composite material according to claim 1, characterized in that: The parameters for the melt grafting described in S2 are: temperature 165-195℃, duration 2-6min. The homogenization process described in S2 has the following parameters: temperature 170–190°C, duration 1–3 min.

7. The reactive extrusion preparation method of a polylactic acid energy metering box composite material according to claim 1, characterized in that: The drying process described in S3 has the following parameters: temperature 80–100℃, vacuum degree -0.09MPa, and duration 4–12h.

Citation Information

Patent Citations

  • Polylactic acid shell of electric energy metering box and preparation method of polylactic acid shell

    CN114806117A

  • Polylactic acid packing materials having ultraviolet protection function and ultraviolet irradiation degradation resistance performance

    CN105199349A

  • Polylactic acid based composite material and preparation method thereof

    CN108774384A